If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 3x + 17 = 73 + 5x Reorder the terms: 17 + 3x = 73 + 5x Solving 17 + 3x = 73 + 5x Solving for variable 'x'. Move all terms containing x to the left, all other terms to the right. Add '-5x' to each side of the equation. 17 + 3x + -5x = 73 + 5x + -5x Combine like terms: 3x + -5x = -2x 17 + -2x = 73 + 5x + -5x Combine like terms: 5x + -5x = 0 17 + -2x = 73 + 0 17 + -2x = 73 Add '-17' to each side of the equation. 17 + -17 + -2x = 73 + -17 Combine like terms: 17 + -17 = 0 0 + -2x = 73 + -17 -2x = 73 + -17 Combine like terms: 73 + -17 = 56 -2x = 56 Divide each side by '-2'. x = -28 Simplifying x = -28
| 4x-3=-24 | | 98=-10 | | 28x+2= | | 4(-x+5)=2(x+7)-6x | | 5x-4=-3x+12-2x | | 3x+6=6x+9-7x | | -5a+7+4a=-(a+7) | | F(x)=2(x^2-9x+5)-5(x-k) | | n+40=41 | | -5a-7+4a=-(a+7) | | 6x-5=x^2+4 | | Y=sqrt(x-4)+5 | | 2x+3x=1000 | | 2x+80=152 | | n+12=13n | | x=4509307201 | | -7x=-154 | | n+8-n=9n-n | | 5a+7-4a=-(a+7) | | 5+-1v+4v=1+5v+3 | | n+8=9n | | -5a+7-4a=-(a+7) | | -3x^2-10x+5=0 | | 6x=-14x | | -105+8x+6x^2+x^3=0 | | 4x^2+8x=38-6y^2 | | 2xy*3-60+x=6xy*10 | | -(-15x)-3= | | xy=3x^2-6+y | | 9x+4x-6x-5=2 | | 108=12X^2 | | 3x+5x-6x-5=5 |